Supporting children’s health needs: an analysis of paid leave policies in 193 countries - Amy Raub; Jody Heymann (Global Public Health, 2023)
ABSTRACTThe COVID-19 pandemic has highlighted the extent to which national laws and policies shape public health and economic security. Paid leave policies enable parents to meet children’s health needs while maintaining job and income security. These policies matter immensely to children’s health every year. Yet, little is known about the extent to which policies exist to support the full range of childhood health needs. Using a novel dataset constructed from legislative text in 193 countries, this study assesses whether laws in place in 2019 are adequate to support meeting children’s everyday, serious, and disability-related health needs. Globally, only half of the countries guaranteed working parents access to any paid leave that could be used to meet children’s health needs. Only a third addressed everyday health needs, including leave that matters to reducing infectious disease spread. For serious health needs, even when paid leave was available, it was often too short for complex health conditions. Moreover, although all children require parental presence at medical appointments and for serious illness, fewer countries guaranteed paid leave to care for older children than younger. Addressing these gaps is crucial to supporting child health and working families during times of public health crisis and every year.